2004
DOI: 10.1002/app.20428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the high‐density polyethylene melt index on the microcellular foaming of high‐density polyethylene/polypropylene blends

Abstract: ABSTRACT:The effect of high-density polyethylene (HDPE)/polypropylene (PP) blending on the crystallinity as a function of the HDPE melt index was studied. The melting temperature and total amount of crystallinity in the HDPE/PP blends were lower than those of the pure polymers, regardless of the blend composition and melt index. The effects of the melt index, blending, and foaming conditions (foaming temperature and foaming time) on the void fractions of HDPEs of various melt indices and HDPE/PP blends were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 41 publications
4
72
0
2
Order By: Relevance
“…In this manner, and because of its higher crystallinity and its role in reducing spherulite sizes, PE functions as a stiffener for the PP matrix. It is reported that a higher PP content in a blend leads to a higher void fraction compared to samples with a lower PP content [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…In this manner, and because of its higher crystallinity and its role in reducing spherulite sizes, PE functions as a stiffener for the PP matrix. It is reported that a higher PP content in a blend leads to a higher void fraction compared to samples with a lower PP content [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…The foam morphology is related to a structure of polymers -the most important are branchings in the polymer chain and crystallinity (Huang et al, 2008;Rachtanpun et al, 2004;Su & Huang, 2010;Li et al, 2007). It is well established that foaming is easier with amorphous polymers like PS than with crystalline ones like polyolefines.…”
Section: Technology Of Polymer Foamingmentioning
confidence: 99%
“…Until now, the research on microcellular foams has been mainly directed at polystyrene, 10 -18 polypropylene, 19 poly(methyl methacrylate), 20 polyamide, 21 polysulfone, 9,22,23 poly(ether sulfone), 23,24 poly(ether imide), 24 or their blends. [25][26][27][28][29][30][31] Only a few studies have been conducted on the preparation of microcellular polycarbonate (PC) foam, 5,32,33 one of the most important engineering plastics. Because of weak melt strength and melt elasticity, its foaming is more difficult than other plastics.…”
Section: Microcellular Foam Was Invented At the Massachusettsmentioning
confidence: 99%